Choices available for implementing smart grid communication network - Farooq, H. (Institute of Electrical and Electronics Engineers Inc., 2014)
Communication network is considered to be a vital component and cornerstone of smart grids. It is envisaged that design of communication network will be the most challenging task for transforming ageing power grid into a modern smart grid. Many communication technologies existing today can be utilized for enabling communication among smart grid entities, however, each one of them has its own tradeoffs which needs to be considered. Hierarchically, smart grid communication network is made up of three area networks each having its own requirements and limitations. It is, therefore, necessary to analyze the communication technologies in perspective of these three area networks of smart grids. This paper presents the choices available for enabling communication in respective area networks of smart grids. Moreover, performances of IEEE 802.11 and IEEE 802.15.4 standards are evaluated using NS-2 simulations for deployment of multi-hop ad-hoc architecture of smart grid communication network. Â© 2014 IEEE.